Making Sense of Infant Familiarity and Novelty Responses to Words at Lexical Onset - DePaolis, Rory A.; Keren-Portnoy, Tamar; Vihman, Marilyn (Frontiers in Psychology, 2016)
This study suggests that familiarity and novelty preferences in infant experimental tasks can in some instances be interpreted together as a single indicator of language advance. We provide evidence to support this idea based on our use of the auditory headturn preference paradigm to record responses to words likely to be either familiar or unfamiliar to infants. Fifty-nine ten-month-old infants were tested. The task elicited mixed preferences: familiarity (longer average looks to the words likely to be familiar to the infants), novelty (longer average looks to the words likely to be unfamiliar) and no-preference (similar-length of looks to both type of words). The infants who exhibited either a familiarity or a novelty response were more advanced on independent indices of phonetic advance than the infants who showed no preference. In addition, infants exhibiting novelty responses were more lexically advanced than either the infants who exhibited familiarity or those who showed no-preference. The results provide partial support for Hunter and Ames’ (1988) developmental model of attention in infancy and suggest caution when interpreting studies indexed to chronological age.